TO ASSESS THE INFLUENCE OF DOUBLE REDUCTION POLICY ON THE LEARNING ABILITY, SUBJECT SCORES AND STRESS LEVELS OF JUNIOR & MIDDLE SCHOOL STUDENTS - Qiang Wang; Ping Jiang (Fonseca, Journal of Communication, 2024)
Objective: The impacts of the double reduction policy on understudies’ cognitive limits, critical thinking, problem-solving skills, scholastic inspiration, and branch of knowledge test brings about Junior and middle school are the focal point of this exploration. Methodology: A sum of 200 children, educators, and guardians were overviewed utilizing a mix of methods. Quantitative estimations, for example, scholarly commitment scores and subject scores, and subjective bits of knowledge from meetings and center gatherings were utilized to decide the policy’s adequacy. A measurable investigation of the information shows that while scholastic commitment scores truly do ascend after the policy is instituted, this might be because of chance as opposed to the actual policy. Results: The policy might not affect scholarly commitment, however an ANOVA shows that there is a significant contrast in scores between courses. The connection grid additionally uncovers promising positive relationship between scholastic excitement, knowledge, and problem-solving aptitudes both when the policy was ordered. This demonstrates that the policy could impact these variables together. The greatness of the thing that matters was estimated utilizing the t-test measurement, which returned a worth of 8.234. The critical p still up in the air to be 0.955. This p-esteem, which is far higher than the commonly acknowledged 0.05 edge, demonstrates that the noticed changes in students’ level of scholarly commitment are almost certain the result of chance than of the double reduction methodology. Conclusion: This study gives important experiences into the complicated elements inside educational conditions through a top to bottom assessment of the impact of the double reduction policy on the educational system, students’ cognitive skills, critical thinking, problem-solving abilities, scholastic commitment, and subject scores.The outcomes give new understanding into the mind boggling elements at play in the impacts of the double reduction policy